The Effect of Marketing Strategy and Medical Representative Relationships on the Achievement of Sales Targets through Doctors’ Prescription Decisions in Indonesian Healthcare Services - Hendri Hendri; Zaharuddin Zaharuddin; Sitta Kusuma Freddy (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
This study aims to analyze the influence of marketing strategy and Medical Representative (MR) Relationships on The sales targets of ethical products at PT Bayer Indonesia, with doctor's prescribing Decisions as a mediating variable. The pharmaceutical industry possesses unique characteristics where doctors act as The primary decision-makers in drug utilization, making The role of The Medical Representative (MR) crucial. This research adopts a quantitative explanatory approach. Data were collected through surveys and analyzed using The Structural Equation Modeling - Partial Least Squares (SEM-PLS) method. The results indicate that marketing strategy and Medical Representative (MR) Relationships have a positive and significant impact on doctors' prescribing Decisions and The achievement of sales targets. Furthermore, The doctor's prescribing Decision is proven to be a significant mediating variable that bridges The influence of marketing strategy and MR Relationships on sales targets. These findings underscore that success in achieving sales targets in The pharmaceutical industry heavily depends on The effectiveness of marketing communication strategies and The quality of professional Relationships built by The field force with clinicians.